2019
DOI: 10.1515/cdbme-2019-0099
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an azide-modified extracellular matrix by adipose-derived stem cells using metabolic glycoengineering

Abstract: Natural extracellular matrix (ECM) represents an ideal biomaterial for tissue engineering and regenerative medicine approaches. For further functionalization, there is a need for specific addressable functional groups within this biomaterial. Metabolic glycoengineering (MGE) provides a technique to incorporate modified monosaccharide derivatives into the ECM during their assembly, which was shown by us earlier for the production of a modified fibroblast-derived dermal ECM. In this study, adipose-derived stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…the outstanding bioactive properties) with abiotic functional groups which are a powerful tool for (bio) conjugation. 10,[17][18][19][20] Characterisation of the successful azide modication of cell-derived ECM via MGE was successfully completed by covalently linking clickECM azides to an alkynecoupled uorophore via Huisgen 1,3-dipolar azide-alkyne cycloaddition 10,18-20 (ESI Fig. 1 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the outstanding bioactive properties) with abiotic functional groups which are a powerful tool for (bio) conjugation. 10,[17][18][19][20] Characterisation of the successful azide modication of cell-derived ECM via MGE was successfully completed by covalently linking clickECM azides to an alkynecoupled uorophore via Huisgen 1,3-dipolar azide-alkyne cycloaddition 10,18-20 (ESI Fig. 1 †).…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17] Using the same monosaccharide but adipose-derived stem cells (ASCs) instead of broblasts, Nellinger et al demonstrated that this method can be used to generate azide-modied tissue-specic ECM. 18 As an alternative to the above mentioned Ac 4 -GalNAz, Gutmann et al demonstrated the successful modication of NIH-3T3 broblasts-derived ECM using the glucosamine derivate 2-azidoacetylamino-2-deoxy-(1,3,4,6)tetra-O-acetyl-D-glucopyranoside (Ac 4 GlcNAz). 19,20 Despite the successful modication of ECM with azides via MGE and their demonstrated applicability as surface coatings or bioconjugation platforms, 10,17,19 it is not yet understood if MGE changes properties of azide-modied ECM (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials, in general, attempt to mimic these multifactorial aspects of ECM function; however, synthetic materials and single ECM components fail to achieve the molecular complexity and organization of the ECM in vivo. , Therefore, the use of complex CDMs as biomaterialsin addition to decellularization of whole tissues and organs , has recently gained attention because they promise to preserve, at least to a large extent, the complexity of native tissue matrices. ,,, However, these biological matrices still lack specific addressable functional groups, which are often required for their use as a biomaterial. , …”
Section: Introductionmentioning
confidence: 99%
“…Later, Gutmann et al used a similar method to successfully modify the ECM of NIH3T3 fibroblasts using the glucosamine derivate 2-azidoacetylamino-2-deoxy-(1,3,4,6)-tetra- O -acetyl- d -glucopyranoside (Ac 4 GlcNAz) . More recently, Nellinger et al modified the ECM from adipose-derived stem cells (ASCs) with azides through MGE using the above-mentioned Ac 4 GalNAz …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we [9] and others [10] reported the preparation of a functionalized ECM by MGE. For example, we demonstrated the incorporation of azide functionalities into the ECM of human fibroblasts [9a] and ASCs, [9b] which can be addressed via bioorthogonal copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) [11] . We demonstrated different possible applications of the azide‐modified ‘clickECM’ and showed, for example, the positive effect of a clickECM coating on the fibroblast culture and demonstrated the clickECM as a bioconjugation platform using biotin‐streptavidin interaction [12] …”
Section: Introductionmentioning
confidence: 99%